FAMILY ENVIRONMENT AND INDIVIDUAL EMOTIONAL STABILITY (Educa Journal of Studies, 2026)
This article provides a psychological analysis of the impact of family environment on an individual’s emotional stability. The system of family relationships, parenting styles, and emotional support within the family and their influence on a person’s psychological state are examined. In addition, the effects of both positive and negative family environments on an individual’s stress resilience, self-confidence, and emotional regulation are discussed on a scientific basis.
Keywords: Family environment, emotional stability, stress, personality psychology, upbringing, psychological support, self-confidence.